Standards of corporate moral responsibility: The role of opinion leaders - Slutskiy, Pavel; Ordeix, Enric; Polo López, Marcos (Opción, 2016)
This research is focused on the role that opinion leaders play in changing moral standards and in setting the agenda for corporate moral responsibility, as well as on highlighting those organizations that fail to conform to moral standards. There is a demand for independent moral validation of corporate decisions, actions and initiatives. In response to this demand opinion leaders try to provide credible and objective information that appears to be more trustworthy since opinions leaders are assumed to be beyond corporate control. Independence and regular public exposure make opinion leaders influential enough to set the benchmarks and basic requirements for corporate moral standards.